The Role of Composition and Visual Balance in Still Life Painting - Tolibova Umida Davlat qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
ANNOTATION: This article explores the role of composition and visual balance in still life painting, emphasizing their importance in developing students’ artistic perception and creative skills. The study discusses pedagogical methods for teaching students to create balanced compositions, identify focal points, and achieve harmony among objects using principles of shape, color, and spatial relationships. Shovdirov S.A.’s research on visual arts education serves as a methodological foundation for the study.